Radiative edge cooling experiments in Wendelstein 7-X start-up limiter campaign. (24th May 2019) - Barbui, T.; Effenberg, F.; König, R.; Krychowiak, M.; Schmitz, O.; Baldzuhn, J.; Blackwell, B.D.; Buttenschön, B.; Drews, P.; Jakubowski, M.; Kwak, S.; Liang, Y.; et al.
Abstract: Impurity seeding experiments during the start-up limiter campaign of Wendelstein 7-X provide first evidence for a localization effect of the 3D magnetic edge structure on the seeded impurities and their radiation distribution and cooling effect. Moreover, species dependencies have been seen. Nitrogen was observed to cool the entire edge plasma, with a stronger electron temperature reduction measured at the downstream position at the limiter. The radiation was limited at the periphery of the confined region. Both the temperature reduction and the radiation enhancement were directly correlated to the injection of the coolant gas. Mitigation of the limiter heat loads was also measured. Neon was observed to affect also the confined plasma with a long-lasting radiation and a cooling of the entire plasma.